KONSEP PENGEMBANGAN ISTANA ASSERAYAH AL-HASYIMIAH SIAK SRI INDRAPURA PROVINSI RIAU BEDASARKAN ANALISIS KARAKTERISTIK DAN MOTIVASI WISATAWAN - Siregar, Aisyah Astinadia (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Asserayah Al-Hasyimiah Palace is a tourist destination that displays the stylistic architecture of Malay, Arab, and European as well as wide range of royal heritage collections which have the potential to bring in tourist. Structurally, the Palace of Asserayah Al-Hasyimiah is under the office of youth tourism and sports of Siak Regency. The purpose of this research is to identify the potential tourist attraction in the Palace of Asserayah Al-Hasyimiah as well as to identify the concept of development that can be applied by providing a number of recommendations to increase tourism visits. This research uses descriptive method which is analyzed based on tourists' characteristics and motivations through data collection, data reduction, data display, verification, and conclusion. This research is conducted by means of direct observation to the location, interviews, literature studies, and questionnaires involving 100 respondents. Research result based on the characteristics and motivations of tourists shows that the Palace of the Asserayah Al-Hasyimiah has three major groups of development concept; namely, the development of the attraction, management, and promotion of the Palace of Asserayah Al-Hasyimiah.